In-situ biological regeneration of zeolite to enhance the treatment of high ammonia-nitrogen wastewater by partial nitrification - CHEN Xu; YANG Xiaofan; WANG Chenggang; KUANG Naiqiang; CHEN Chunfu; ZHANG Liqiu (Gongye shui chuli)
In order to solve the problem of high concentration of free ammonia(FA) inhibiting ammonia oxidizing bacteria and causing high concentration of ammonia nitrogen wastewater to be unable biologically treated, natural zeolite was used to alleviate the inhibitory effect of FA. Natural clinoptilolite was added to SBR for partial nitrification treatment of copper-ammonia wastewater with ammonia-nitrogen of 210 mg/L. On the 86th day of operation, the reactor achieved 98.5% of ammonia-nitrogen removal rate at load of 1.105 kg/(m3·d). In-situ biological regeneration during the reaction process ensured the continuous enhancement effect of natural zeolite, with zeolite regeneration rates of 99.0% to 106.3%. Through the analysis of extracellular polymeric substance(EPS) content and composition of sludge, it was found that the increase of influent ammonia-nitrogen led to the increase of EPS content, and protein mass fraction in EPS was increased under the stress of copper ion, which promoted the formation of sludge granulation. High throughput sequencing results showed that Nitrosomonas was the main ammonia-oxidizing functional bacterium genus, with relative abundance varied from 10.3% to 51.7%. Comamonas rapidly increased in the presence of high concentration of ammonia-nitrogen, with relative abundance increasing from 0.6% on the 22nd day to 29.9% on the 86th day. The partial nitrification was strengthened by natural zeolite to realize stable and high-efficient treatment of copper-ammonia wastewater.